Psycho-physiological aspects of small combats in taekwondo: impact of area size and within-round sparring partners - Ouergui, I.; Ardigò, L.; Selmi, O.; Chtourou, H.; Bouassida, A.; Franchini, E.; Bouhlel, E. (Biology of Sport, 2021)
The study investigated physiological and psychological responses to taekwondo combat sessions as a function of different area sizes and within-round sparring partners. Twenty-four adolescent (age: 17 ± 1years) male (n = 12) and female (n = 12) taekwondo athletes participated in the study. Each athlete confronted 1 (1vs.1; no sparring partner change) or 2 (1vs.2; within-round sparring partner change every minute) opponents in different area sizes (i.e., 4 × 4 m, 6 × 6 m, and 8 × 8 m) for 2 min. Blood lactate concentration ([La]) was measured before and after bouts. Heart rate (HR) was measured throughout the contests and rating of perceived exertion was assessed after bouts. Mean HR (HRmean) and percentage of maximum HR (%HRmax) determined during a 20-m multistage shuttle run test were used for analysis. Mood states were assessed before and after bouts and physical enjoyment was analyzed after bouts. The results showed higher HRmean and %HRmax values for the 1vs.1 compared to the 1vs.2 condition (p < 0.001) and [La] values were higher at post-combat measurements (p < 0.001). Moreover, tension and fatigue were higher in 6 × 6 m compared with 8 × 8 m (p = 0.022 and p=0.023,respectively) and anger was higher in 6×6 m and 8×8m in comparison with 4×4m (p=0.012 and p = 0.043, respectively). Confusion increased from before to after bouts (p < 0.001), from 4 × 4 m and 6 × 6 m area sizes to 8 × 8 m (p = 0.001 and p = 0.018, respectively), and from 1vs.1 to 1vs.2 (p < 0.001). Furthermore, vigour decreased from before to after bouts (p < 0.01). Taekwondo combat sessions are a specific conditioning exercise for athletes. Thus, coaches can use the 1vs.1 condition to elicit higher HR responses and 6 × 6 m area size to induce higher psychological stress, mimicking what occurs during a competition.